The effect of endometriosis on the antimüllerian hormone level in the infertile population - Romanski, Phillip A.; Brady, Paula C.; Farland, Leslie V.; Thomas, Ann M.; Hornstein, Mark D. (Journal of assisted reproduction and genetics, 2019)
Purpose To determine whether the presence of endometriosis in infertile women without prior ovarian surgery influences markers of ovarian reserve, AMH and FSH. Methods A retrospective cohort study included three groups of women who presented for IVF treatment at our tertiary care center from 04/27/2015 to 05/31/2017: women with endometriosis and prior ovarian surgery (EnSx), women with endometriosis without prior ovarian surgery (En), and women with a primary diagnosis of male factor infertility (MF; reference group). Results There were 671 patients that met inclusion criteria (78 EnSx, 60 En, and 533 MF). Compared to the MF group (3.6 ± 3.0), a lower mean AMH level (ng/mL) was observed in the EnSx group (2.5 ± 2.5; aβ − 1.21; 95% CI [− 1.79, −0.62]) and in the En group (2.5 ± 2.2; aβ − 1.11; 95% CI [− 1.68, − 0.54]). Both endometriosis groups had a statistically significantly higher proportion of patients with an AMH < 1 (EnSx, 24.4%; OR, 2.39 [95% CI, 1.31, 4.36]; En, 28.3%; OR, 2.67 [95% CI, 1.41, 5.08]) compared to the MF group (13.9%). The mean baseline FSH level (lU/L) was statistically significantly higher in both endometriosis groups (EnSx, 8.6 ± 4.3; β , 1.37 [95% CI, 0.39, 2.34]; En, 8.4 ± 3.7; β , 0.96 [95% CI, 0.04, 1.87]) compared to the MF group (7.3 ± 2.2). Conclusions Among infertility patients with endometriosis, with and without a history of ovarian surgery, ovarian reserve markers were worse (lower AMH and higher FSH) and a higher proportion had decreased ovarian reserve as measured by AMH compared to women with MF.